Feminist Male Communication Experience in Revealing Gender Identity in the Campus Environment (Literasi Nusantara, 2025)
This study explores the communication experiences of feminine male students at Trunojoyo University, Madura, a region characterized by conservative and religious norms. Utilizing a qualitative phenomenological approach, the research examines how three purposively selected informants navigate their gender identity within a dominant masculine culture. Data were gathered through in-depth interviews, observations, and documentation. The findings reveal that informants express femininity through both verbal and non-verbal communication, including soft speech patterns, refined gestures, neat aesthetics, and high emotional openness. However, these expressions are highly contextual; while informants are authentic in "safe spaces" or among supportive peers, they often perform communication adjustments in formal or public settings to mitigate social stigma and negative labeling. Key factors enabling identity disclosure include robust self-acceptance, social support systems, and the university’s relatively inclusive academic climate. The study concludes that gender identity is not a static trait but a dynamic, negotiated process. It highlights the tension between individual authenticity and cultural expectations, emphasizing that the campus serves as a critical site for negotiating identity through continuous social interaction.
Keywords: Communication Experience; Feminine Men; Gender Identity